GENERATIVE AI USE, SELF-REGULATED LEARNING, AND EFL WRITING READINESS: TESTING A MEDIATION MODEL AMONG EFL LEARNERS - Fitriani Fitriani; Ratu Noorita Achmad (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2026)
This study examined the effect of generative artificial intelligence (AI) use on English as a Foreign Language (EFL) learners' writing readiness (WR), and tested whether this effect is mediated by self-regulated learning (SRL). A quantitative correlational design was employed, using data collected through an online questionnaire. 168 EFL learners from universities in Eastern Indonesia completed an online questionnaire. Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS was used to test the measurement model and the hypothesized structural relationships, including the mediating role of SRL. The results show that generative AI use has a positive but non-significant direct effect on writing readiness, whereas AI use significantly and positively predicts self-regulated learning, and self-regulated learning significantly and positively predicts writing readiness. The indirect effect of AI use on writing readiness through SRL is significant, indicating that SRL fully mediates the relationship between generative AI use and EFL writing readiness. These findings suggest that the benefit of generative AI for writing readiness is not automatic but is channeled through learners' capacity for self-regulation; the cross-sectional design and the specific EFL learner population may limit generalizability. This study contributes new empirical evidence on the psychological mechanism linking generative AI use to EFL writing outcomes, positioning self-regulated learning as the key mediating pathway, and offers practical guidance for integrating generative AI into EFL writing instruction.